Pola Asuh Dharma Komunal Sebagai Praktik Sosio-Religius Masyarakat Hindu Lombok dalam Membentuk Karakter Generasi Berkelanjutan - Ida Bagus Heri Juniawan; Ida Bagus Alit Arta Wiguna; Ni Putu Sasmika Dewi; Ni Nyoman Satya Widari (Jayapangus Press, 2026)
Social change and the dynamics of modernity pose challenges to the sustainability of character values among the younger generation, including within religious communities rooted in local traditions. Although studies on Hindu upbringing have expanded, research specifically examining the communal dimensions of upbringing in Lombok’s Hindu society and its connection to the formation of a sustainable generation remains limited. This study aims to analyze communal dharma upbringing as a socio-religious practice of the Lombok Hindu community in shaping the character of a sustainable generation. The study employs a qualitative, descriptive-analytical design. Data were collected through in-depth interviews, participatory observation, and documentary analysis within Hindu communities in West Lombok, Central Lombok, North Lombok, and the city of Mataram. Research findings indicate that communal dharma-based parenting is carried out through the collective involvement of families, banjars, temples, and pasramans, with values internalized through practice via role modeling, ritual participation, ngayah, and communal work. Hindu values such as dharma, Tri Kaya Parisudha, Tri Hita Karana, bhakti, ahimsa, and yadnya are internalized in children’s daily experiences and shape a character encompassing spiritual, social, personal, and ecological dimensions. This study concludes that communal dharma parenting is a community-based value-transmission system relevant to the character formation of future generations and has the potential to serve as a reference for developing culture- and religion-based parenting models within the context of sustainable human development.